2021
DOI: 10.4491/eer.2021.368
|View full text |Cite
|
Sign up to set email alerts
|

Game theoretic approach for flood risk management considering a financial model

Abstract: In process of flood risk management, there is usually conflict between the governments, insurance companies and people as players in sharing financial responsibilities, because of how calculate insurance premium, compensation and governmental assistances. In order to this conflict resolution, in this paper a new methodology is proposed based on game theoretic approach by using Nash equilibrium method, that for the first time, the payoff functions of insurance companies and government have been associated to ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Moreover, among the studies identified that used HEC-FDA for flood damage analysis, it is noted that none of them developed a study based on past land use, which can be compared with the results of this study (Cunha and Taveira-Pinto, 2011;Qi and Altinacar, 2011;Mohammadi et al, 2014;Lee et al, 2015;Mas, 2015;Difrancesco et al, 2020;Moosakhaani et al, 2020;Moosakhaani, et al, 2022). However, Van Dau et al (2017)…”
Section: Urban Growthmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, among the studies identified that used HEC-FDA for flood damage analysis, it is noted that none of them developed a study based on past land use, which can be compared with the results of this study (Cunha and Taveira-Pinto, 2011;Qi and Altinacar, 2011;Mohammadi et al, 2014;Lee et al, 2015;Mas, 2015;Difrancesco et al, 2020;Moosakhaani et al, 2020;Moosakhaani, et al, 2022). However, Van Dau et al (2017)…”
Section: Urban Growthmentioning
confidence: 94%
“…Some studies that used HEC-FDA, for evaluating flood damage proposed plans with mitigation measures, such as dams, flood insurance, and different channel types. In these studies, benefits were found with the application of protective measures, such as a reduction in expected annual damage (Lee et al, 2015;Mas, 2015;Moosakhaani et al, 2020). In a study carried out in the Bago region of Myanmar, it was observed that there were elevated houses, with average heights between 1.4 and 1.9 m, indicating that this type of house was mostly located in highly flood-prone areas, aiming to adapt to flooding.…”
Section: Flood Mitigation Measuresmentioning
confidence: 99%
See 1 more Smart Citation